Genetic diversity assessment of Hopea hainanensis in Hainan Island - Chen, Yukai; Zhang, Hai-Li; Zhang, Li; Nizamani, Mir Muhammad; Zhou, Taoxiu; Zhang, Haiyang; Liu, Tingting (Frontiers in Plant Science, 2022)
Hopea hainanensis (Dipterocarpaceae) is an endangered tree species restricted to Hainan Island, China, and a small part of Northern Vietnam. On Hainan Island, it is an important indicator species for tropical forests. The wood of Hopea hainanensis has a very high utilization value in nature since it is compact in structure, hard in texture, not easily deformed after drying, durable, and resistant to sunlight and water. As a result of its high quality, it has been felled and mined by humans without restraint, resulting in a reduction of its population size, severe habitat fragmentation, and a sharp decline in its population. Therefore, its conservation biology needs to be researched urgently. Researchers are currently focusing on the ecological factors and seed germination in the habitat of Hopea hainanensis to determine its endangered status. In the literature, there are no systematic analyses of the endangered mechanism of Hopea hainanensis in terms of genetic diversity. It focuses especially on the systematic genetic diversity of Hopea hainanensis in fragmented habitats. Using single nucleotide polymorphism (SNP) and genotyping-by-sequencing (GBS) technology, 42 samples from seven different cohabitation groups were genotyped. The results showed that the average heterozygosity of the six populations of Hopea hainanensis was 19.77%, which indicated that the genetic diversity of Hopea hainanensis was low. Genetic diversity research is essential for rare and endangered plant protection research. We can find a scientific basis for protecting endangered plants on slope bases by analyzing genetic differences and relationships among populations.